Ice thickness and bed elevation maps derived from radar and GPS profiles over three ice rises (Blåskimen Island, Kupol Ciolkovskogo and Kupol Moskovskij) in Western Dronning Maud Land - Goel, Vikram; Matsuoka, Kenichi (Norwegian Polar Institute, 2019)
This dataset provides ice thickness calculated using deep-sounding (2 MHz antenna frequency) radar profiles over three ice rises Blåskimen Island, Kupol Ciolkovskogo and Kupol Moskovskij, Fimbul Ice Shelf, western Dronning Maud land. Ice thickness was estimated by converting the two way travel time of the radar signal from surface to the bed. The calculation takes into account the increased propagation speed in the top surface firn layer (method described in Goel et. al., 2017). The dataset also provides the bed elevation along the same profiles, obtained by subtracting ice thickness from surface elevation data. The data are provided in MATLAB (.mat) files named: * Kupol Ciolkovskogo: IRB_IceThickness.mat * Kupol Moskovskij: IRC_IceThickness.mat * Blåskimen Island: IRD_IceThickness .mat Each file includes following arrays: * ‘LAT’ and ‘LON’ shows the coordinates as per WGS84 ellipsoid in decimal degrees * ‘X’ and ‘Y’ shows the coordinates in polar stereographic projection parallel to 71°S (EPSG 3031) * ‘IT’ and ‘BE’ shows the ice thickness and bed elevation in meters * ‘XX’, ‘YY’, ‘TT’ and ‘BB’ are matrices with interpolated gridded x-coordinate, y-coordinate, ice thickness and bed elevation data respectively See the following manuscript for method details: Goel, V., Brown, J., and Matsuoka, K.: Glaciological settings and recent mass balance of Blåskimen Island in Dronning Maud Land, Antarctica, The Cryosphere, 11, 2883-2896, https://doi.org/10.5194/tc-11-2883-2017, 2017.